Islamic thought in the twentieth century/ edited by Suha Taji-Farouki and Basheer M. Nafi - "Taji-Farouki, Suha (ed.)" (London, 2004)
This book provides in-depth discussions of Islamic thought across the 20th century, encompassing the breadth of self-expression in Muslim communities world-wide. It explores key themes in modern Islamic thinking including the social origins and ideological underpinnings of the late 19th- early 20th-century Islamic reformist project, nationalism in the Muslim world, Islamist attitudes towards democracy, the science of Islamic economics, Islamist notions of family and the role of women, Muslim perceptions and constructions of the West, and aspects of Muslim thinking on Christians and Jews. It elucidates the emergence, evolution and importance of these themes in terms of the historical, political and social conditions of the Muslim world, and its ongoing interactions with the West. Informed by an appreciation of the unprecedented changes experienced by Muslim societies and culture since the late 19th century, its overall framework challenges more simplistic approaches to Islamic thought, and to its makers and producers. This book is an excellent source for modern and contemporary Islam, politics and international relations, and the modern history of the Muslim world.
Keywords: Islamic religion